Trends and patterns of 2013 curriculum research in physical education: Bibliometric analysis from 2013-2020 - Novri Gazali; Romi Cendra; Hafid Dwi Saputra; Norazlinda Binti Saad; M E Winarno; Yulingga Nanda Hanief; Khairul Hafezad Abdullah; Mohd Izwan Shahril; Singha Tulyakul (Lambung Mangkurat University, 2021)
The implementation of the 2013 curriculum in physical education learning in schools is an issue that has emerged in recent years. The main objective of this study is to conduct a systematic analysis of trending research literature, especially on the topic of the 2013 curriculum in physical education, using bibliometric analysis. This study uses a bibliometric analysis approach with the help of the VOS Viewer application. The articles’ search results show that the study of the 2013 curriculum in physical education totaled 106 articles which were published from 2013-2020 using three databases, namely Scopus, Google Scholar and Dimensions. Then, the researchers conducted a filter that was only limited to journal articles and proceedings, and checked for duplication of articles. Based on the checking, it was found that the same 8 articles were published in the three databases, so that the final result was 89 articles. Based on the VOS Viewer mapping, the findings reveal that: the number of publications from 2013 to 2020 has increased; of the 89 published articles, all of the authors are from the State of Indonesia, because the topics discussed (Curriculum 2013) are the education curriculum in Indonesia; ME Winarno (State University of Malang) was the author with the most publications (6 documents); the sources that published the most articles were Advances in Social Science, Education and Humanities Research (12 documents); the most influential article (77 citations) is entitled